A Conceptualisation of the Sharing Economy: Towards Theoretical Meaningfulness - Miguel, Cristina; Martos-Carrión, Esther; Santa, Mijalche (Springer International Publishing, 2022)
AbstractThe sharing economy aims to redistribute existing goods (e.g., tools, cars) across the population in order to maximise their functionality. Within sharing economies, there can be monetary exchange (e.g., Airbnb, BlaBlaCar), or the exchange can be altruistic (e.g., Timebanking, CouchSurfing). Nevertheless, sharing economy platforms mainly function as digital marketplaces where supply and demand are matched. The rise of sharing economy practices is followed by a torrent of publications. As a result, there is conceptual confusion about the sharing economy concept. This chapter aims to provide an answer to this challenge by following the framework for theoretical meaningfulness. Through two levels of literature analysis, the chapter aims to shed light on the conceptualisation of the sharing economy.
Keywords: Collaborative economy, Conceptualisation, Peer-to-peer, Digital platforms, Sharing economy